Obediência ao princípio da sobrecarga no treinamento resistido e melhora da autonomia funcional em idosos (2021)
The objective was to compare strength and functional autonomy among elderly practitioners of resistance training with and without additional overload. 28 elderly men and women from the open-air gym and LERES / UEPA participated. Methods: Handgrip strength was assessed through dynamometry, lower limb resistance from the sit-and-stand test in 30 seconds and functional autonomy by the GDLAM test battery. The results showed slightly higher levels for the measurement of handgrip strength and lower limb resistance in the Leres group that practices resistance training with progressive overload. In the GDLAM protocol, although without statistical differences, the LERES group performed the C10M, LPS, LCLC and VTC tests in slightly lower times than the AAL group, presenting a higher time only in the LPDV test, therefore with better functional autonomy, proving that the elderly are more functionally active due to the greater muscle strength and endurance resulting from structural adaptations caused by progressive overload. It is concluded that, through the practice of resistance exercise, favorable responses can be obtained regarding the levels of functional autonomy in the elderly, significantly improving muscle strength gain, thus causing greater independence and better quality of life.